Determination of Heat Transfer Coefficients for French Plastic Semen Straw Suspended in Static Nitrogen Vapor Over Liquid Nitrogen - Santos, Maria Victoria (2015)
BACKGROUND: The use of mathematical models describing heat transfer during the freezing process is useful for the improvement of cryopreservation protocols. A widespread practice for cryopreservation of spermatozoa of domestic animal species consists of suspending plastic straws in nitrogen vapor before plunging into liquid nitrogen. Knowledge of surface heat transfer coefficient (h) is mandatory for computational modelling; however, h values for nitrogen vapor are not available. OBJECTIVE: In the present study, surface heat transfer coefficients for plastic French straws immersed in nitrogen vapor over liquid nitrogen was determined; vertical and horizontal positions were considered. MATERIALS AND METHODS: Heat transfer coefficients were determined from the measurement of time-temperature curves and from numerical solution of heat transfer partial differential equation under transient conditions using finite elements. The h values experimentally obtained for horizontal and vertically placed straws were compared to those calculated using correlations based on the Nusselt number for natural convection. RESULTS: For horizontal straws the average obtained value was h=12.5 ± 1.2 W/m2 K and in the case of vertical straws h=16 ± 2.48 W/m2 K. The numerical simulation validated against experimental measurements, combined with accurate h values provides a reliable tool for the prediction of freezing curves of semen-filled straws immersed in nitrogen vapor. CONCLUSION: The present study contributes to the understanding of the cryopreservation techniques for sperm freezing based on engineering concepts, improving the cooling protocols and the manipulation of the straws.